Implementasi Pengamanan PGP Pada Platform Zimbra Mail Server - Pramana Hostiadi, Dandy; Suradarma, Ida Bagus (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 1 April 2017DO - 10.24843/LKJITI.2017.v08.i01.p05, 2017)
Electronic mail is a communication model that is fundamental in the era of globalization. Proven on any form of registration data or information requires the presence of email address(electronic mail). The use of email itself cannot be separated from the abuse (such as stelling password and mail spoofing) from some parties so it needs security form in email communication. Communication security on mail server such as ZIMBRA mail server has been well-implemented, such as the use of ssl certificate.  But the security is still standard.  So, when user and password have been found out by third party, email content will be read easily (in cryptography technique it is called plaintext reading). On research that was conducted with pretty good privacy (PGP) method email communication security was focused on the email content by encrypting mail text along with the attachment file. In a study conducted, using the mail engine Zimbra mail server. Result of research shows that PGP security is able to secure email content whether the text or the attachment, showing difference of attachment file size is bigger on PGP using and change mail header from the standard mail.
Keywords: E-mail, Zimbra Mail Server, PGP, Enkripsi.